Methodology for assessing adaptive cruise control behavior. - Bareket, Z. (IEEE Transactions on intelligent transportation systems)
This paper reports on nonintrusive methods for characterizing the longitudinal performance of vehicles equipped with adaptive cruise control (ACC) systems. It reports the experimental set-up and procedures for measuring ACC system performance, followed by the modeling and simulation of the measured ACC performance. To further assess the interaction of ACC vehicles with human-controlled traffic, microscopic simulation involving both a human-driver model and an ACC model is discussed.